Morphological traits and nutritional value of six local cultivars of maize (Zea mays) from Gorontalo, Indonesia - NOVRI YOULA KANDOWANGKO; MARGARETHA SOLANG; FEBRIYANTI FEBRIYANTI; AISYAH AHMAD (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Kandowangko NY, Solang M, Febriyanti, Ahmad A. 2025. Morphological traits and nutritional value of six local cultivars of maize (Zea mays) from Gorontalo, Indonesia. Biodiversitas 26: 2289-2298. Maize local varieties are grown in Gorontalo, Indonesia, namely doti, siropu, momala, kiki, pulo and damahu. The existence of this corn is utilized by the community to make various types of traditional processed foods such as binthe biluoto, balobinthe. However, this local corn is starting to be rarely found. The morphological traits and nutritional benefits of these six indigenous corns have not been extensively researched. This research aimed to characterize the morphology of local corn plants and analyze their nutritional value. Descriptive and quantitative analysis. The findings of the analysis indicated that local maize plants have different traits. The height of the plant ranges from 115-195 cm, the number of leaves is between 11-15, and the seeds are orange (Zea mays var. doti), orange red tip (Z. m. var. siropu), marron red (Z. m. var. momala), white (Z. m. var. pulo), clear white (Z. m. var. damahu). The composition of the nutritional value of local corn is as follows: Water content 6.69-15.69%; Ash content 0.92-2.48%; Fat content 2.85-5.09%; Protein content 8.82-12.53%, Carbohydrate ranges from 71.22-77.22; Amylosa 7.46-22.00%. Reduction sugar 0.54-1.92%, In addition, local corn contains high levels of Zn, K, and Mg minerals. The existence of local corn that is rich in nutrients needs to be preserved so that it can support the development of food products to meet human nutritional needs.